2021
DOI: 10.5194/bg-18-535-2021
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of ozone and drought stress on the emission of biogenic volatile organic compounds from <i>Quercus robur</i> L.

Abstract: Abstract. Drought events are expected to become more frequent with climate change. To predict the effect of plant emissions on air quality and potential feedback effects on climate, the study of biogenic volatile organic compound emissions under stress is of great importance. Trees can often be subject to a combination of abiotic stresses, for example due to drought or ozone. Even though there is a large body of knowledge on individual stress factors, the effects of combined stressors are not much explored. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 147 publications
(136 reference statements)
4
20
0
Order By: Relevance
“…Our study demonstrated a classic reduction of photosynthetic rate ( A ) by water stress due to diminished g s and CO 2 availability ( Figure 3 and Figure 4 ) as observed in numerous studies [ 26 , 36 , 86 ], and this reduction was only moderately enhanced by O 3 exposure ( Figure 3 A). This further emphasizes that reduced g s prior to O 3 exposure protects photosynthetic machinery and results in a lower effective O 3 dose as observed also in other studies [ 23 ].…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Our study demonstrated a classic reduction of photosynthetic rate ( A ) by water stress due to diminished g s and CO 2 availability ( Figure 3 and Figure 4 ) as observed in numerous studies [ 26 , 36 , 86 ], and this reduction was only moderately enhanced by O 3 exposure ( Figure 3 A). This further emphasizes that reduced g s prior to O 3 exposure protects photosynthetic machinery and results in a lower effective O 3 dose as observed also in other studies [ 23 ].…”
Section: Discussionsupporting
confidence: 84%
“…O 3 also activates the production of reactive oxygen species (ROS) [ 18 , 19 ], which in turn activate various defense reactions related to non-volatile and/or volatile metabolites depending on the plant species and genotype [ 20 , 21 , 22 , 23 , 24 ]. Characteristically, O 3 exposure leads to emissions of methanol and lipoxygenase (LOX) pathway volatiles due to damaged cell walls and cell and organelle membranes [ 23 , 25 ] and might also result in emissions of the stress hormone methyl salicylate [ 20 , 23 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations